Pengaruh Kombinasi Jumlah Piston dan Turbin Terhadap Performa Pembangkit Listrik Tenaga Mekanisme Oscillating Water Column - Pratama, Fideryan Axel; Ulum, Miftahul; Noerpamoengkas, Ardi (Universitas Trunojoyo Madura, 2023)
The need for electrical energy is very high, but fossil power plants are running low. Consequently, innovations in alternative energy sources are increasing, including sea waves. The geographical location of Indonesia, which is a country with several islands and is accompanied by several beaches, has the potential to bring up innovations in alternative renewable energy, namely wave power plants. In Indonesia, several regions have used sea wave power plants with the OWC (Oscillating Water Column) system. Therefore, this study conducted an experimental OWC test of a piston and turbin as combination mechanism in a water wave power plant by combining the number of pistons and turbines in 3 variations, i.e., 1 piston with 2 turbines, 1 piston with 1 turbine, and 2 pistons with 1 turbine. This experiment compared the effects of the combination of the number of pistons and turbines on the torque, voltage rotation, mechanical power, electrical power, and efficiency of the three combinations. The research results indicated that the combination of 1 piston and 1 turbine produced the highest torque of 4.73 Nm, while the combination of 1 piston and 2 turbines yielded 0.76 Nm, and 2 pistons and 1 turbine generated 4.47 Nm. Out of the three combinations, the highest electrical and mechanical power occurred in the combination of 1 piston and 1 turbine at 8 watts and 298.4 joules per second, respectively, with a voltage of 0.89663 volts, a rotation of 603 rpm, and an efficiency of 10%.